Aspen Simulation Of Methylene Blue Adsorption Using Coconut Shell Based Activated Carbon - Zainol, Nurhidayah (Universiti Sains Malaysia, 2021)
Methylene Blue (MB) is a cationic dye that has been found in wastewater. In this project, the adsorption of MB through dynamic simulation was carried out and the simulation data were validated with the experimental result. It was analyzed based on the effect of initial concentration, flow rate, and bed height at constant temperature 303.15 K. According to predicted breakthrough curves, MB is adsorbed in greater amounts on coconut shell activated carbon and has high saturation time at lower initial concentration, lower flow rate and higher bed height in all experimental and simulation. The breakthrough curves were analyzed using Thomas, Bohart-Adams, and Yoon-Nelson models under different conditions. The linear form of the models was used to fit the experimental and simulation data. Linear regression analysis for both data indicated that each model has its significant characteristics such as adsorption capacity (Thomas model), rate constant (Bohart-Adams model) and 50% breakthrough (Yoon-Nelson model). The results showed that both experimental and simulation data well represented by Thomas model, while both Bohart-Adams and Yoon-Nelson model were also found adequate for explaining the dynamic behaviour of the column. The R2 value for simulation data close to unity, however the R2 for experimental data is poor for Thomas model. The model proposed by simulation data has a better fit than the experimental results. In any case, the overall model is encouraging, implying that the accuracy assumptions, equations, and estimated model parameters are appropriate.